Rebel Guerrillas Mosby, Quantrill and Anderson - Williams, Paul 1946- (McFarland & Company, Inc., Publishers, 2018)
"From the Eastern Confederate States to Missouri and "Bleeding Kansas," a vicious war was fought behind the big-battle clashes of the American Civil War. John Singleton Mosby became renown for hit-and-run tactics of his rebel horsemen. William Clarke Quantrill and William "Bloody Bill" Anderson became notorious for their savagery"...
Includes bibliographical references and index
Keywords: Mosby, John Singleton -- 1833-1916; Quantrill, William Clarke -- 1837-1865; Anderson, William T. -- 1840-1864; Anderson, William T. -- 1839-1864; Quantrill, William C. -- 1837-1865; Guerrillas -- Confederate States of America -- Biography; Soldiers -- Confederate States of America -- Biography; United States -- History -- Civil War, 1861-1865 -- Biography; Biografie